Digital Memory and Children’s Right to Health: Reinterpreting the Right to Be Forgotten - seyednasseri, mohammadMehdi (Bioethics and Health Law Journal (BHL), 2026)
The persistence of personal data in digital environments has created new challenges for the protection of children’s fundamental rights, particularly the right to health understood as encompassing psychological well-being, personal development and dignity. This study examines the right to be forgotten as an emerging legal mechanism capable of safeguarding children’s right to health in the age of permanent digital memory. This research adopts a doctrinal and analytical-descriptive approach in international law. Relevant legal instruments, judicial decisions and interpretative documents including the Convention on the Rights of the Child and the jurisprudence of the Court of Justice of the European Union are examined to evaluate the normative relationship between the right to be forgotten and the child’s right to health. The analysis demonstrates that the right to be forgotten functions not only as a data protection mechanism but also as a preventive safeguard against psychological harm, reputational damage and long-term developmental risks arising from the permanent accessibility of childhood data. A child-centered interpretation of this right strengthens the protection of mental health, identity formation and informational autonomy. The study concludes that the right to be forgotten should be recognized as an integral component of the child’s right to health in the digital environment. Effective realization of this right requires child-oriented legal standards, enhanced platform accountability and accessible mechanisms enabling children to regain control over their digital identities.